PERJUANGAN IDEOLOGI DALAM FATWA (Studi Terhadap Fatwa Tarjih Muhammadiyah) - Mohammad Hasan Bisyri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
This article analyzes the ideological struggle in the fatwas of the Muhammadiyah Legal Affairs Committee. Ideology contained in Fatwas Tarjih different ideologies that are in the mainstream of Islamic law (fiqh) in the society. In general, Fiqh give attention to men (dominant groups), while Muhammadiyah fatwa Tarjih attention to marginalized groups. The emergence of such a fatwa is not simply due to the proposition (Nas), but there is a certain ideology that strives for, which is to defend the marginalized groups. They are women and children who have often become victims in under the hand marriage and illegal divorce.